Draft Genome Sequences of Itaconate-Producing Ustilaginaceae - Geiser, Elena (Genome Announc, 2016)
Some smut fungi of the family Ustilaginaceae produce itaconate from glucose. De novo genome sequencing of nine itaconate-producing Ustilaginaceae revealed genome sizes between 19 and 25 Mbp. Comparison to the itaconate cluster of U. maydis MB215 revealed all essential genes for itaconate production contributing to metabolic engineering for improving itaconate production.